ENVIRONMENTAL DISPLACEMENT IN INTERNATIONAL LAW: BEYOND THE REFUGEE CONVENTION, WITHIN THE HUMAN RIGHTS FRAMEWORK - Nadia Moumou,; Fatiha Bennamane, (International Journal of Innovative Technologies in Social Science, 2025)
The category of environmentally displaced persons does not fall within the scope of protection provided by the 1951 Geneva Refugee Convention, as environmental factors are not recognised as grounds for asylum. Moreover, no specific international treaty protects this new category of refugees. Despite this legal gap, scholars have sought to define the concept of environmental refugees to find solutions to the issue of ecological displacement, relying on two fundamental principles: human dignity and the principle of non-discrimination. Some general provisions for protecting refugees in international human rights law are also invoked. In this context, certain United Nations bodies, particularly the United Nations High Commissioner for Refugees (UNHCR) and the Human Rights Committee, have increasingly played a role in addressing environmental displacement.